Effects of a weight loss plus exercise program on physical function in overweight, older women: a randomized controlled trial - Anton SD (Dove Medical Press, 2011)
Stephen D Anton1,2, Todd M Manini1, Vanessa A Milsom2, Pamela Dubyak2, Matteo Cesari3, Jing Cheng4, Michael J Daniels5, Michael Marsiske2, Marco Pahor1, Christiaan Leeuwenburgh1, Michael G Perri21Department of Aging and Geriatric Research, University of Florida, Gainesville, FL, USA; 2Department of Clinical and Health Psychology, University of Florida, Gainesville, FL, USA; 3Area di Geriatria, Università Campus Bio-Medico, Rome, Italy; 4Division of Oral Epidemiology and Dental Public Health, San Francisco, CA, USA; 5Department of Statistics, University of Florida, Gainesville, FL, USABackground: Obesity and a sedentary lifestyle are associated with physical impairments and biologic changes in older adults. Weight loss combined with exercise may reduce inflammation and improve physical functioning in overweight, sedentary, older adults. This study tested whether a weight loss program combined with moderate exercise could improve physical function in obese, older adult women.Methods: Participants (n = 34) were generally healthy, obese, older adult women (age range 55–79 years) with mild to moderate physical impairments (ie, functional limitations). Participants were randomly assigned to one of two groups for 24 weeks: (i) weight loss plus exercise (WL+E; n = 17; mean age = 63.7 years [4.5]) or (ii) educational control (n = 17; mean age = 63.7 [6.7]). In the WL+E group, participants attended a group-based weight management session plus three supervised exercise sessions within their community each week. During exercise sessions, participants engaged in brisk walking and lower-body resistance training of moderate intensity. Participants in the educational control group attended monthly health education lectures on topics relevant to older adults. Outcomes were: (i) body weight, (ii) walking speed (assessed by 400-meter walk test), (iii) the Short Physical Performance Battery (SPPB), and (iv) knee extension isokinetic strength.Results: Participants randomized to the WL+E group lost significantly more weight than participants in the educational control group (5.95 [0.992] vs 0.23 [0.99] kg; P < 0.01). Additionally, the walking speed of participants in the WL+E group significantly increased compared with that of the control group (reduction in time on the 400-meter walk test = 44 seconds; P < 0.05). Scores on the SPPB improved in both the intervention and educational control groups from pre- to post-test (P < 0.05), with significant differences between groups (P = 0.02). Knee extension strength was maintained in both groups.Conclusion: Our findings suggest that a lifestyle-based weight loss program consisting of moderate caloric restriction plus moderate exercise can produce significant weight loss and improve physical function while maintaining muscle strength in obese, older adult women with mild to moderate physical impairments.Keywords: obesity, weight loss, physical function, oxidative stress, inflammation, walking speed